OPEN TRACHEOSTOMY IN ORAL AND MAXILLOFACIAL SURGERY IN A RESOURCE LIMITED SETTING: THE HOPE OF WHOM LITTLE IS GIVEN - Rowland Agbara; Benjamin Fomete; Obiadazie Athanasius-Chukwudi; Omeje Uchenna-Kelvin; Onyebuchi Polycarp; Idowu Enoch Abiodun (Peytchinski Publishing, 2018)
Purpose: Despite advances in anaesthetic techniques, health resource environment still face challenges in achieving safe anaesthesia due to limited facilities and skilled personnel. This study highlights the value of open tracheostomy in oral/maxillofacial surgery in a health resource-limited setting. Materials and Methods: Maxillofacial surgery patients who had a tracheostomy in a regional University Teaching Hospital between February 1999 and August 2017 were retrospectively studied. Details sourced included age, sex, surgical condition, indication for tracheostomy and complications. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 16 (SPSS Inc., Chicago, IL, USA). Findings from descriptive statistics were represented in the form of tables and charts. Results: A total of 51 patients had an open tracheostomy and this consisted of 28 (54.9%) males and 23 (45.1%) females. The main anaesthetic indication was preoperative difficult airway assessment, and there was more elective (n=45; 88.2%) than emergency tracheostomies. Orofacial tumours (n=30; 58.9%) were the major conditions managed. More patients with mallampati class IV (n=18; 69.2%) had tracheostomy. About 98.0% (n=50) of the patients had a temporary tracheostomy and the main complications noted were mortality, surgical emphysema and haemorrhage. Conclusion: In resource-limited environments, the maxillofacial surgical team frequently has little facility to work with and often face challenging cases. Although these patients can be safely anaesthetized using less invasive methods in health resource-rich settings, tracheostomy offers surgeons in our environment an opportunity to improve the quality of life of these patients who otherwise cannot be safely anaesthetized due to limited facilities or skilled manpower.